The big snow - Hader, Berta; Hader, Elmer, 1899- (New York : Aladdin Paperbacks, 1993)
Despite their elaborate preparations for the winter, the animals and birds are delighted by a surprise banquet after a big snow.
Caldecott Medal/Honor.
Library Journal.
Wilson's Children.
Library Journal, June 2000.
Wilson's Children, November 1996.
3.2.
Keywords: Animals -- Fiction; Winter -- Fiction; Animals -- Fiction; Winter -- Fiction